Studies on genesis of chromite and PGE in Naein ophiolite melange - Reza Shamsipour Dehkordi; Maryan Sadeghi; Zohreh Gholami Fesharaki (Journal of Economic Geology, 2012)
Nain ophiolite melange is located 140 Km east of Isfahan. Based on the geological studies, this area belongs to Mesozoic ophiolite of Urumieh – Dokhtar zone, west of central Iran. Country rocks are pridotite and serpentinized pridotite. The pridotite rocks are composed of Harzburgite, Lherzolite and replacement Dunite which is belong to spinel pridotite facies. Paragenesis of ore minerals are Chromite, Irarsite, Magnetite, Hematite, Pentlandite, Millerite, Chalcopyrite, Pyrite, and Covelline. Geochemical surveys of host rock and chromite show tholeiite series of magma and alpine type chromite. PGE (Ir, Pt, Pd, and Os) are enriched in chromite. REE spider diagram pattern show the processes of boninitic magma and partial melting.